Fecal Calprotectin Use in Inflammatory Bowel Disease and Beyond: A Mini-Review - Bashaar Alibrahim; Mohammed I Aljasser; Baljinder Salh (Canadian Journal of Gastroenterology and Hepatology)
Given the number of inflammatory disorders affecting the gastrointestinal tract directly and indirectly, coupled with the considerable overlap with functional disorders, it is evident that more useful noninvasive diagnostic tests are required to aid with diagnosis. If these tests can also have some utility for individual patient follow-up in terms of disease activity and response to treatment, as well as providing forewarning of disease relapse, it would be extremely useful information for the clinician. One recently described test that may fulfill several of these attributes is based on leakage of a mononuclear cell cytoplasmic protein, calprotectin, along the intestinal tract, which can then be quantified in feces. This has been used to distinguish patients exhibiting symptoms of irritable bowel syndrome from patients with inflammatory bowel disease, with a measure of success greater than with currently used techniques. The present article summarizes the experience with this test used in inflammatory bowel disease, as well as a variety of gastrointestinal disorders.